Equality of Opportunity for Children in Egypt, 2000-2009 : Achievements and Challenges - Vélez, Carlos E. (World Bank, Washington, DC, 2012)
This paper provides relevant indicators and measurements useful for public policies seeking the expansion of equitable human development opportunities for Egyptian children and youth. To measure equitable access to opportunities, the authors use the Human Opportunity Index to examine the evolution of 16 basic opportunity indicators grouped in four sectors: education, basic housing services, early childhood development, and nutrition and hunger. The main findings show that during the last decade most opportunities for children and youth improved unambiguously,for the first two sectors, but were stagnant for nutrition and early childhood development opportunities. Although the urban-rural and interregional gaps were partially reduced, there are still substantial opportunity gaps between children in favorable and unfavorable circumstances. Parents' education, income per capita, urban-rural location, number of siblings, and regional location, are the five most important factors affecting equality of opportunity, although their impact varies across indicators.